TECHNIQUES WRITING LESSON PLAN (RPP) - Yayan Sudrajat (Peneliti.net, 2018)
Writing a Lesson Plan (RPP) can only be done if the lecturer has written a Semester Lesson Plan (RPS). The Lesson Plan is the smallest learning program that contains a plan for the delivery of a particular subject to plan the expected final ability (KAD). The formulation of the Lesson Plan format that will be made at least consists of the identity of the course, the expected final ability, learning activities, learning media, learning resources, and assessment instruments.